An urban, community-based whole of systems approach to address childhood overweight and obesity. (30th September 2020) - Wardle, K; Maitland, N; Allender, S; Jalaludin, B; Haigh, F
Abstract: Background: In 2015 two billion people were estimated to be above a healthy weight globally, contributing to a rapid increase of non-communicable diseases. Evidence indicates multi-faceted and community-led interventions are most effective in addressing the complexity of childhood overweight and obesity. Campbelltown - Changing our Future is a practical example of an urban, community-based whole of system approach to identify, develop and implement community-led interventions to address this issue. Methods: Key community stakeholders and leaders, who had power to change environments and norms, were engaged in a series of three workshops to develop a systems map. A Group Model Building (GMB) framework was used across the workshops to facilitate community perception of the key factors that compose the system that influences childhood overweight and obesity within an urban community. Community members were asked to identify and commit to community-led actions to effect change on various elements of the system. Results: Over 200 community members were engaged in the GMB process, establishing the following systems map themes: physical activity and sedentary behaviour, healthy eating, knowledge and education and social factors. A further 200 community members are contributing to 90 ongoing community-led comprehensive interventions to address childhood overweight and obesity. Conclusions: Over 90 actions are active within the community, ranging from high profile athletes' role modelling reading to children through to a Council healthy food and drink policy. These actions contribute to creating change across multiple levels of the system, an effective, sustainable solution to addressing childhood overweight and obesity. Key messages: Practical implementation of a whole of system approach in an urban community produces community-led action. A whole of systems approach facilitates community engagement to address complex issues.